Teacher Education in Ghana - Patrick Swanzy; Sandra Maria Gadelha de Carvalho; José Ernandi Mendes Mendes (Linguagem em Foco, 2025)
Teacher education is recognized as a vital component for the socio economic development of every country. This is because the academic and professional standards of teachers constitute a critical component of the essential learning conditions for achieving the educational goals of a nation. Being aware of these, Ghana embraced teacher education and the sector has since evolved. However, the development in Ghana’s teacher education sector has not been mapped, analysed, synthesised and shared with the scholarly community in a single paper. This paper critically reviews literature (reports, policy texts, working papers, government documents and statistical data from government agencies) on the most significant developments in Ghana’s teacher education from past to the present and prescribe the desired teacher education for the future.